Artificial Intelligence Adoption and Psychological Factors Shaping Employee Mental Well-Being - Yuliantinus Gibrani Anandera Perlampura; Fatmah Bagis; Tri Septin Muji Rahayu; Alfato Yusnar Kharismasyah (CV. Creative Tugu Pena, 2025)
Digital transformation through the adoption of artificial intelligence (AI) is increasingly changing the dynamics of modern work and creating new psychological risks for employees. This study aims to analyze the influence of AI Adoption on Depression, as well as to test the role of Psychological Safety as a mediator and Ethical Leadership as a moderator in this relationship. Using a quantitative approach with SEM-PLS, this study involved 195 employees from the financial sector, selected through purposive sampling with a minimum tenure of one year. The results show that AI adoption has a positive effect on depression and also has an impact on psychological safety. Furthermore, psychological safety has an insignificant effect on depression and mediates the relationship between AI adoption and depression. On the other hand, ethical leadership has a positive effect on psychological safety but does not moderate the of AI adoption on psychological safety. These findings indicate that psychological stress due to technology adoption is more influenced by AI-based work demands than leadership factors. Practically, this study emphasizes the importance of strengthening a psychologically safe work environment to minimize the negative impacts of digitalization and support employee mental well-being.